PENGARUH KOMPOSISI FACE-CORE TERHADAP SIFAT FISIK DAN MEKANIS ORIENTED STRAND BOARD DARI BAMBU DAN ECENG GONDOK - Sahriyanti Saad; . Hilal (Forestry Faculty of Universitas Hasanuddin, 2012)
The effect of particle composition made of bamboo and water hyacinth on the dimensional stability and mechanical properties of resulted oriented strand boards (OSB) were investigated. Three layered boards were made from bamboo and water hyacinth in which bamboo strand was used as face/back layer and water hyacinth strand was used as core layer. The boards were manufactured using three levels of bamboo and water hyacinth compositions (50:50, 60:40 and 70:30) with 6 % isocyanate based on the strand oven dry weight. The results showed that dimensional stability of the OSB decreased with the increase of composition of water hyacinth strand on core layer. A higher composition of bamboo strand as face/back layer compared to water hyacinth strand resulted in increased modulus of elasticity and internal bond strength, but decreased the modulus of rupture. The bamboo and water hyacinth composition of 70:30 compositions showed better properties than other compositions. Key words: Bamboo, water hyacinth, composition, OSB